2019
DOI: 10.1101/599266
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Deficiency in the autophagy modulator Dram1 exacerbates pyroptotic cell death of Mycobacteria-infected macrophages

Abstract: AbstractDNA Damage Regulated Autophagy Modulator 1 (DRAM1) is a stress-inducible regulator of autophagy and cell death. DRAM1 has been implicated in cancer, myocardial infarction, and infectious diseases, but the molecular and cellular functions of this transmembrane protein remain poorly understood. Previously, we have proposed DRAM1 as a host resistance factor for tuberculosis (TB) and a potential target for host-directed anti-infective therapies. In this study, we generated … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
24
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 10 publications
(26 citation statements)
references
References 71 publications
(69 reference statements)
2
24
0
Order By: Relevance
“…Moreover, we found that DRAM1 was involved in maintaining normal organization of the Golgi apparatus, suggesting that DRAM1 plays a role in Golgi functions 15 . It was recently reported that acidification of mycobacterium marinum (Mm)-containing vesicles was strongly reduced in DRAM1 mutants in tuberculosis (TB) model 16 . In the current study, we found that DRAM1 was decreased in NSCLC and negatively correlated with EGFR levels.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, we found that DRAM1 was involved in maintaining normal organization of the Golgi apparatus, suggesting that DRAM1 plays a role in Golgi functions 15 . It was recently reported that acidification of mycobacterium marinum (Mm)-containing vesicles was strongly reduced in DRAM1 mutants in tuberculosis (TB) model 16 . In the current study, we found that DRAM1 was decreased in NSCLC and negatively correlated with EGFR levels.…”
Section: Introductionmentioning
confidence: 99%
“…In order to verify the results obtained using morpholino-mediated knockdown, we studied S. Typhimurium infection in a recently established dram1 mutant line (Zhang et al, 2020). We infected dram1 -/-and dram1 +/+ embryos with S. Typhimurium ( Figure 3A) and observed that dram1-/hosts showed increased mortality during S. Typhimurium infection as compared to dram1+/+ controls ( Figure 3B).…”
Section: Dram1 Mutation Recapitulates the Infection Phenotype Of Drammentioning
confidence: 87%
“…Similarly, induction of the zebrafish homolog of DRAM1 ( dram1 ) by Mycobacterium marinum infection relies on the TLR adaptor molecule MyD88 (van der Vaart et al, 2014). M. marinum -infected zebrafish embryos develop a tuberculosis-like disease and we have shown that Dram1 plays a host protective role in this model (van der Vaart et al ., 2014; Meijer and van der Vaart, 2014; Zhang et al ., 2020). Specifically, we found that knockdown of dram1 strongly reduces the co-localization of Lc3 with M. marinum , whereas overexpression increases Lc3- M. marinum co-localization in a manner dependent on the selective autophagy receptor p62 (Meijer and van der Vaart, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations